Comorbidity of paraphilia and depression in Mexico - Christian Haasen (Mental Illness)
The comorbidity of paraphilia-related disorders and other psychiatric disorders is high, but the paraphilia-related disorder often remains untreated until patients seek help for the comorbid disorder. A case of a patient in Mexico with comorbid paraphilia and depressive disorder, who was effectively treated with antidepressive medication and psychotherapy, is reported. The effect of stigmatization of homosexuality on the access to care of persons with sexual disorders is discussed.